Revitalization of the Role of Majelis Taklim Mushola Nurul Iman Bukit Gading in Male Religious Study to Enhance Religious Awareness in Cangkudu Village, Balaraja District, Tangerang Regency - Mansurudin; Ahmad Badruddin (IRDH International Journal of Social Sciences & Humanities, 2025)
The revitalization program of the Taklim Assembly at the Mushola Nurul Iman Bukit Gading is a community service effort aimed at reinvigorating the spirit of the congregation, particularly the male members, in religious study sessions and enhancing religious awareness in the village of Cangkudu, Balaraja District, Tangerang Regency. The activities are conducted over eight weeks using interactive seminar methods and participatory discussions. This approach is chosen to address the issues of declining congregation participation, monotonous study methods, and the lack of relevance of topics discussed to the needs of the congregation. The evaluation results show an increase in the attendance of congregants from an average of 24 people before the program to 42 people after the program. The scores for religious understanding also significantly increased from an average of 62 to 84 on a scale of 100. The highest increase occurred in the understanding of the father's role in the family (38%), followed by the management of Sharia finance (32%), and value-based emotional management (29%). Positive impacts are also seen in the behavioral changes of congregants at home and the increase in religious-based social activities in the surrounding area of the mosque. The limitations of facilities and the variation in work schedules of the congregation are the main obstacles in the implementation of this program. Therefore, follow-up actions such as strengthening facilities, digital training for the administrators, and the preparation of simple learning modules are recommended to support the sustainability of the program.